A method to measure nanomechanical properties of biological objects - Ploscariu, Nicoleta; Szoszkiewicz, Robert (My University, 2014)
We postulate that one will be able to quantitatively infer changes in the mechanical properties of proteins, cells, and other biological objects (BO) by measuring the shifts of several thermally excited resonance frequencies of atomic force microscopy cantilevers in contact with BOs. Here, we provide a method to extract spring constants and molecular damping factors of BOs in biologically relevant phosphate buffered saline medium and using compliant AFM cantilevers with a small aspect ratio (a ratio of length to width).
Keywords: Biological objects; Measurement; Atomic force microscopy; Spring constants; Molecular damping factors